ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH DAN KEMANDIRIAN DAERAH (Studi Pada Kabupaten/Kota di Provinsi Bengkulu) - lndah Permata Sari; Lisa Martiah Nila Puspita (JURNAL FAIRNESS, 2022)
This research aims to : (1) test and describe positive influence government spending against Income of the original area (PAD) district/city of Bengkulu province: (2) test and describe per capita income against the positive influence of the original Regional Revenue (PAD) district/city of Bengkulu province : (3) test and describe positive influence population against the original Revenue Areas (PAD) district/city of Bengkulu province and (4) testing and describe positive influence of the original regional income against the independence County/City of Bengkulu province. Sample research is the district/city of Bengkulu province. Methods of data analysis using multiple regression analysis. From the results of the research note that: (1) Government spending proved to be positive and significant effect against the original revenue district/city of Bengkulu province. This means that high government spending is very influential on improving native : (2) the income per capita is not proven to have an effect on the revenue of the original County/City of Bengkulu province. This means that percapita income changes on society, do not affect the original improvement area : (3) population growth/no effect against the original revenue district/city of Bengkulu province. This means that changes in population does not affect the oroginal improvement areas and (4) of the original Regional Revenue (PAD) proved to be positive and significant effect against the independence of the County/City of Bengkulu province. This means that high PAD level greatly affects the independence area.